2019
DOI: 10.3389/fphys.2019.01195
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Interval Training Impacts Muscle and Brain Oxygenation Responses to Incremental Exercise

Abstract: The purpose of the present study was to assess the effects of aerobic interval training on muscle and brain oxygenation to incremental ramp exercise. Eleven physically active subjects performed a 6-week interval training period, proceeded and followed by an incremental ramp exercise to exhaustion (25 W min–1). Throughout the tests pulmonary gas exchange and muscle (Vastus Lateralis) and brain (prefrontal cortex) oxygenation [concentration of deoxygenated and oxygenated hemoglobin, HHb and O2Hb, and tissue oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…(e) the level of cognitive load [209][210][211][212], (f) the level of cognitive fatigue [213][214][215], (g) the influence of stress [216][217][218][219][220], (h) the influence of expertise level [104,122,212,221] or skill level [106,222], (i) training-related changes in motor-cognitive performance [105,117]. Accordingly, the provided evidence further buttresses the idea to use brain-derived parameters in exercise prescription.…”
Section: Advantages Of Brain-derived Indicators Of Internal Loadmentioning
confidence: 61%
See 1 more Smart Citation
“…(e) the level of cognitive load [209][210][211][212], (f) the level of cognitive fatigue [213][214][215], (g) the influence of stress [216][217][218][219][220], (h) the influence of expertise level [104,122,212,221] or skill level [106,222], (i) training-related changes in motor-cognitive performance [105,117]. Accordingly, the provided evidence further buttresses the idea to use brain-derived parameters in exercise prescription.…”
Section: Advantages Of Brain-derived Indicators Of Internal Loadmentioning
confidence: 61%
“…However, these demands are mirrored in brain-derived measures. Regarding fNIRS-derived brain parameters, it was reported that they are sensitive to: the level of cognitive load [ 209 , 210 , 211 , 212 ], the level of cognitive fatigue [ 213 , 214 , 215 ], the influence of stress [ 216 , 217 , 218 , 219 , 220 ], the influence of expertise level [ 104 , 122 , 212 , 221 ] or skill level [ 106 , 222 ], training-related changes in motor–cognitive performance [ 105 , 117 ]. …”
Section: Advantages Of Brain-derived Indicators Of Internal Loadmentioning
confidence: 99%
“… Wang et al (2010) found hypoxic training does not affect muscle [O 2 Hb] response to hypoxic exercise nor cerebral NIRS parameters during normoxic exercise, despite a ∼50% improvement in maximal workload (+22 ml.min –1 .kg V̇O 2 max) in their participants. Recently, Caen et al (2019) showed aerobic training increased the amplitude of muscle totHb and HHb responses during incremental exercise in normoxia, indicating improved O 2 availability and muscle O 2 extraction with improved fitness. Meanwhile, we found comparable muscle tissue oxygenation responses between Han Chinese and Tibetans during incremental exercise in normoxia, and lower muscle O 2 Hb and totHb in Tibetans during hypoxic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral oxygenation was measured during a maximal incremental test before and after a 6-week cycling training intervention (Caen et al, 2019). Findings revealed that after an aerobic training intervention, participants who displayed greater VO 2max had a higher total [HbO 2 ] and total hemoglobin amplitude during maximal exercise compared to pre-training (Caen et al, 2019).…”
Section: Oxyhemoglobin and Deoxyhemoglobin Following A Training Inter...mentioning
confidence: 98%
“…In the included studies, various terms were used to describe CRF levels. More specifically, the studies evaluating CRF during exercise tasks used terms such as moderately active and sedentary (Brugniaux et al, 2014;Caen et al, 2019), shortterm and long-term training (Buzza et al, 2016(Buzza et al, , 2020, trained and untrained (Oussaidene et al, 2015), endurance athlete and control (Seidel et al, 2019), and athlete and non-athlete (Shibuya and Kuboyama, 2010). In studies measuring cerebral oxygenation during cognitive tasks, the terms higher and lower fit were used to characterize CRF level.…”
Section: Cardiorespiratory Fitness Terminologymentioning
confidence: 99%